Surface plasmon resonance biosensor for the ultrasensitive detection of bisphenol A - Xue, Chadtová Song; Erika, Gedeonová; Jiří, Homola (Analytical and bioanalytical chemistry, 2019)
Bisphenol A (BpA) is a chemical that is extensively used in common plastic products, such as food and drink containers. It can leach from the plastics and penetrate into the human body, where it acts as an endocrine disruptor with significant risks to human health. In order to minimize the exposure of human populations to BpA, methods for the detection of BpA are needed. In this work, we present a novel surface plasmon resonance (SPR) biosensor for ultrasensitive detection of BpA. Our approach combines a binding inhibition assay with functionalized gold nanoparticles for the enhancement of sensor response. We demonstrate that the developed biosensor enables the detection of BpA in a wide range of concentrations (0.01 to 100,000 ng/mL) with an extremely low limit of detection-5.2 pg/mL.
Keywords: fenoly; biosenzitivní techniky; zlato; Phenols; Biosensing Techniques; Limit of Detection; kovové nanočástice; Reproducibility of Results; Surface Plasmon Resonance; Gold; reprodukovatelnost výsledků; limita detekce; povrchová plasmonová rezonance; Benzhydryl Compounds; Metal Nanoparticles; benzhydrylové sloučeniny